Increase Mortality Rate in Sepsis Patients with qSOFA Score Greater than Two - Waqar Khan, Raja Muhammad; Mahmood, Asad; Qayyum, Mohsin; Younas, Zahid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To look for patients of sepsis with a qSOFA score of more than two and an association of a high qSOFA score with mortality and other socio-demographic factors.Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Medicine, Combined Military Hospital, Sialkot Pakistan, from Nov 2021 to May 2022.Methodology: All baseline and relevant investigations were carried out at the time of initial clinical assessment, and the qSOFA score was calculated by a consultant medical specialist for all the patients diagnosed with the septic condition. Patients were followed up for two weeks to look for mortality.Results: A total of 500 patients, managed for sepsis during the study period were included in the study. Of them, 298(59.6) were males, while 202(40.4) were females. Out of all the patients in the study, 379(75.8) had a qSOFA score of two or less than two, while 121(24.2) had a qSOFA score of more than two. Increased mortality, patients with more than 50 years and comorbid illnesses were found statistically significantly more in the group having a qSOFA score of more than two (p-value